PENGARUH LEVEL PUPUK N,P,K TERHADAP KOMPONEN TANAMAN BRACHIARIA HUMIDICOLA CV.TULLY DAN PENNISETUM PURPUREUM CV.MOTT DI AREAL PERTANAMAN KELAPA - Turangan, Dewi; Kaunang, Charles L.; Rumambi, Agnitje; Rustandi, D. (Universitas Sam Ratulangi, 2014)
EFFECT OF N,P,K FERTILIZER LEVELS ON PLANT COMPONENTS OF BRACHIARIA HUMIDICOLA CV.TULLY AND PENNISETUM PURPUREUM CV.MOTT IN COCONUT PLANTATIONS. In North Sulawesi there are vast grasslands as pastures so that breeders only utilize the existing land in the coconut plantations as cattle raising area. Existing land under the coconut plantation can be utilized or planted variety of agricultural commodities, including forage, where feed was instrumental in the success of Â animal farm. In increasing the productivity of forage among others, animal grass needs to be supported by the physical environment, ideal soil and climate. The problem in this research was the area under coconut cultivation had low soil fertility (marginal), so one alternative was given by way of fertilization. Therefore the NPK fertilization is one of the most alternative method to overcome the low soil fertility. The objective of this study was to determine the effect of the combination of NPK fertilizer levels on plant components of Brachiaria humidicola cv. Tully and Pennisetum purpureum cv.mott in coconut plantations. This research was conducted in the western districts of Malalayang 1, Manado city from October 2013 â€“ February 2014. Factorial design method was performed on the basis of completely randomized design with 4 replications. The result in this study showed that the influence of fertilization was demonstrated for the macro elements NPK fertilization required to increase the component of leaves. These elements were met the needs of forage for ruminants. Otherwise the rod components of both grass types were decreased by more complete combination of macro elements of NPK fertilization. In term of different types of grass, the statistical analysis showed that the leaves of the grass component of Pennisetum purpureum were 153.87 g/plot, significantly higher (P<0.05) than Brachiaria humidicola. The stem components were not significantly different for both types of grass. Therefore, the results of this study showed that both types of grass treatment elements required the complete NPK macro to get result with higher leaf components. Keywords: Land, Forage, NPK Fertilizer, coconut plantation area